Termination of Construction Works Contract (Case Study on Polytechnics at The Ministry of Finance in 2021) - Johantri, Bagas; Aprilia, Rachma; Yustiani, Syanni (Journal of Economics, Business, and Government Challenges, 2024)
This research aims to identify the causes of contract termination in construction projects within government agencies involved in the procurement of goods and government services. Government procurement of goods and services has its own regulations where changes in regulations and environmental conditions can result in changes in the management of construction work contract implementation. This study is a qualitative-research with a case study on a simple construction project at a polytechnic under the Ministry of Finance. The research uses primary data from interviews and job documentation. Theme analysis is employed in this study. The results indicate that the theme causing contract termination is costs factor that related to mismanagement of cash flow practices. The ease of doing business for suppliers in participating in tenders can result in them taking on more projects than their financial capacity allows. For regulators, this research can serve as preliminary information for the need to strengthen regulations. For participants in government procurement of goods and services, this study provides insights into risk mitigation for detectingcontract terminations.